Burden of chronic obstructive pulmonary disease attributable to ambient ozone pollution across China and its provinces, 1990–2021: An analysis for the Global Burden of Disease Study 2021 - Yixuan Jiang; Fanshu Yan; Haidong Kan; Maigeng Zhou; Peng Yin; Renjie Chen; Jing Ni (Chinese Medical Journal)
Abstract. Background:. Epidemiological studies have demonstrated a causal relationship between ambient ozone (O3) and mortality from chronic obstructive pulmonary disease (COPD), which is the only outcome considered in the Global Burden of Disease Study 2021 for O3. This study aims to evaluate the temporal trend and spatial distribution of the COPD burden attributable to O3 across China from 1990 to 2021. Methods:. The ambient O3 concentrations in China were estimated. Based on the methodology framework and standard analytical methods applied in the Global Burden of Disease Study 2021, we estimated the annual number, age-standardized rate, and percentage of deaths and disability-adjusted life-years (DALYs) from COPD attributable to O3 pollution during 1990–2021 at the national and provincial levels in China. Results:. In 2021, a total of 125.7 (95% uncertainty interval [UI], 26.4–228.3) thousand deaths and 1917.5 (95% UI, 398.7–3504.6) thousand DALYs from COPD were attributable to ambient O3 pollution in China, accounting for 9.8% (95% UI, 2.1–17.0%) and 8.1% (95% UI, 1.8–14.1%) of the total COPD deaths and DALYs, respectively. Generally, a higher burden was observed among males, the elderly, and the population residing in regions with worse health conditions. The age-standardized rates of COPD deaths and DALYs per 100,000 populations ranged from 0.5 (95% UI, 0–1.4) and 8.1 (95% UI, 0.7–20.9) in Hong Kong to 22.8 (95% UI, 3.9–43.5) and 396.6 (95% UI, 68.9–763.7) in Xizang. From 1990 to 2021, there was a notable decrease in the age-standardized rates of COPD-related deaths (68.2%, 95% UI, 60.1–74.9%) and DALYs (71.5%, 95% UI, 63.7–77.6%), especially in regions with poor health conditions. However, the attributable numbers and percentages changed relatively marginally. Conclusions:. Ambient O3 pollution is a major contributor to the COPD burden in China. Our findings highlight the significant spatial heterogeneity across different provinces and underscore the implementation of geographically tailored policies to effectively reduce O3 pollution and alleviate the associated disease burden.